PENGGUNAAN NARKOBA DIKALANGAN WANITA DI DESA GANTING KECAMATAN SALO KABUPATEN KAMPAR - ", Fadli; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in rural districts Ganting salo Kampar district. The purpose of this study was to analyze the social, cultural, and economic as well as the impact it had on the social environment for women to use drugs. Obtain the necessary data in this study, the authors collected data to descend directly to the location of research and observation and do in-depth interviews. Informants in this study amounted to 5 people. The data obtained was processed in the form of descriptive qualitative analysis. The conclusion from this study is the subject of the age of 36-41 years amounted to 4 people, and aged 41 years and over amounted to 1, the average junior high school graduate informants are all Muslim. All informants residing in their own homes and rata2 mendeliong tribes. And as for drivers of women using drugs there are three reasons caused due to suicide, environmental factors, and the availability of drugs. The research of the results are the background factors of women using drugs terdiriri of factors intrinsic and extrinsic factors. Intrinsic factor is composed of : Religion, Family, Intelligence. While extrinsic factors consist of: Intercourse and social environment, education, economy. Drug abuse carried out by women in the analysis by the lack of faith in women causes women to be involved with drug abuse. Tip : For a family, it gives more attention to the families of both women as wives and women as children. For the government, the public should be more concerned about the economic difficulties the women who formed a working group in order to be more independent woman. For the informant, the informant should be more open to their families if they have heavy loads and any issues.Keywords: Impact, Causes and Drugs